Perlindungan Hukum Terhadap Anak yang Berkonflik dengan Hukum dalam Proses Persidangandi Pengadilan Negeri: Studi Tentang Sistem Peradilan Pidana Anak di Pengadilan Negeri Magetan - Nugroho, Michael Last Yuliar Syamriyadi; , Dr. Natangsa Surbakti, SH, MHum; , Dr. Nurhadiantomo (2016)
Many crimes which involve children as actors spread currently. They must account for their actions and shall be processed according to the prevailing laws. This is intended to maintain the public orderliness and security. However, there is a gap between the application of law to the children and that of law to the adults. The children who commit the criminal offenses assume the rights to get a law protection, particularly in the court proceedings. The objectives of this research are to explain: (1) the factors which cause the children to be in conflict with law. (2) the prosecution to the children in conflict with law following the enactment of Law Number: 12 of 2012 regarding Criminal Justice System of Children. (3) the efforts to extend the law protection to the children in conflict with law in the court proceedings. This research used the juridical empirical method with the descriptive analytical approach. Its data consisted of primary and secondary ones. They were collected through in-depth interview and library research and were analyzed by using the qualitative data analysis. The results of research are as follows: 1) The factors which cause the children to commit criminal offenses are economic factor, parental divorce, social environment factor, and information technology advancement. 2) the criminal prosecution to the children in conflict with law following the enactment Law Number: 12 of 2012 regarding Criminal Justice System of Children follows the following provisions: the children whose age is less than 12 years old are returned to their parents/guardians and are included in the education and guidance program the Social Welfare Organizing Agency (LPKS); those who are aged 12 - 14 years old are returned to their parents/guardians and under the care of the LPKS; and those who are aged 15 - 18 years old are subject to principal and additional punishments. 3) The efforts to extend the law protection to the children in conflict with law in the court proceedings are as follows: the children are investigated within familial atmosphere; the court proceedings are closed to the public; the court proceedings are led by one single judge; the proceeding process is done based on the report of community counselors; the children are accompanied by their parents/guardians, legal advisors, and community counselors; and the sentences and sanctions exposed to the children are lighter than those exposed to the adults.